Awareness of smell exercise after smell dysfunction related to COVID-19 in Alahsaa, Saudi Arabia - Khalid A Alyahya; Abdulrahman Khalid Aldrweesh; Alghaydaa Fouad Aldoughan; Sumaia Mohammed Alarfaj; Fatimah Khalid Alabdulqader; Abdullah A Alarfaj (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2022)
Introduction: Coronavirus disease 2019 (COVID-19) is a severe acute respiratory syndrome. Globally, COVID-19 has infected more than 573 million people, with over 6.3 million deaths on July 27, 2022. The symptoms range from cold-like symptoms, cough, fever, shortness of breath, and sore throat; additionally, studies show that patients frequently have problems with smell and taste disorders (STD). Aim: We aim to estimate the prevalence of COVID-19-related anosmia, hyposmia, and parosmia in Alahssa, Saudi Arabia and establish the level of awareness of smell exercises. Patients and methods: This is a cross-sectional study conducted among adults aged 18-60 living in Alahssa, Saudi Arabia. An online questionnaire containing an informed consent form and a survey to collect demographic data, vaccination status, level of loss of smell and taste, and the level of awareness about smell exercises was distributed among all participants who agreed to participate in this study. Results: Five hundred twenty-four adults agreed to participate in this study. When we assessed their awareness of the smelling exercise, it was found that only 115 patients (21.9%) were aware. About 49 patients (61.3%) practiced the smelling exercise, and 55% reported improvements afterward. Conclusion: The prevalences of olfactory and gustatory dysfunction were found to be 54.6% and 52.5%, respectively. Awareness of olfactory training was moderately low among those infected with COVID-19, while 28% of the patients who had experienced olfactory disturbances were aware of this training. Active, collaborative research is essential for describing the natural history and effective therapy of chemosensory impairment in COVID-19.